Clinical features of Omicron variant infection in 445 patients with coronavirus 19 disease - Lihong Yang; Jianfeng Zhong; Weihong Wang; Feng Zhou; Zhaowei Tong; Yifeng Zheng; Xing Chen (Annals of Saudi Medicine)
BACKGROUND: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) can mutate frequently and many new strains have emerged thus far. The clinical and epidemiological characteristics differ with each dominant strain. OBJECTIVES: Obtain an understanding of the clinical characteristics of patients infected with the Omicron variants of the SARS CoV-2. DESIGN: Retrospective cohort SETTINGS: Teaching hospital in China. PATIENTS AND METHODS: Data on sociodemography, signs/symptoms, hospital stay, viral shedding period, comorbidities, treatment options and final outcome were retrieved from hospital electronic medical record. We collected nasopharyngeal samples, laboratory data, and clinical data from patients admitted to the hospital with SARS CoV-2. MAIN OUTCOME MEASURES: Clinical characteristics of the patients infected with Omicron variant of SARS CoV-2. SAMPLE SIZE: 445 patients RESULTS: The median age was 43.0 years with a range from 2 to 75 years. Two-thirds of the participants were male and one-third were female. Almost half of the participants (51.9%) had no symptoms, whereas 48.1% had at least one symptom. Of symptomatic patients, 26.7% had mild symptoms and 21.3% had moderate symptoms. No patients were admitted with severe or critical symptoms. All patients discharged from the hospital after complete recovery without any serious complications or death. The most common symptom was cough followed by sore throat and fever. Less common symptoms were having sputum, stuffy nose, and muscle pain. Rare symptoms were weakness, headache, diarrhea, hemoptysis and nausea/vomiting. CONCLUSIONS: All patients had mild to moderate symptoms. Shortness of breath was not a common symptom among the study group. No patients needed invasive oxygen therapy in this cohort. LIMITATIONS: Single center and retrospective design. CONFLICT OF INTEREST: None.